Mask beneath the Face and the Dialectics of Confinement in Edward Bond’s Plays - Khatoon, Dr Iffat; Khatoon, Dr. Salma (Journal of Research in Humanities, 2023)
Edward Bond’s works characterize a complex array of recurring structural elements that tunnel into all his works leaving a lasting impression of continuity. Recognition of the entrapment of life and humanity in the problems of the contemporary world constitutes Bond’s theatrical idiom. This essay explores the dialectics of confinement in Edward Bond’s plays by focusing on various aspects of physical, mental and societal masks as forms of incarceration. By equating society with an “over determined structure” and in transforming stage into its theatrical counterpart, a confined and sealed place, Bond’s political purpose is to explore life within invisible confines and to discover the sources of human decadence and dehumanization (Rosen 9). This article contends that Bond demystifies the invisible workings of power structures by portraying various forms of confinement and inhibiting forces that pose a constant threat to individual self-hood and the process of dehumanization as a necessary corollary of the process of institutionalization.